Radiology illustrated: hepatobiliary and pancreatic radiology - Choi, Byung Ihn (Radiology Illustrated, 2014)
Radiology Illustrated: Hepatobiliary and Pancreatic Radiology is the first of two volumes that will serve as a clear, practical guide to the diagnostic imaging of abdominal diseases. This volume, devoted to diseases of the liver, biliary tree, gallbladder, pancreas, and spleen, covers congenital disorders, vascular diseases, benign and malignant tumors, and infectious conditions. Liver transplantation, evaluation of the therapeutic response of hepatocellular carcinoma, trauma, and post-treatment complications are also addressed. The book presents approximately 560 cases with more than 2100 carefully selected and categorized illustrations, along with key text messages and tables, that will allow the reader easily to recall the relevant images as an aid to differential diagnosis. At the end of each text message, key points are summarized to facilitate rapid review and learning. In addition, brief descriptions of each clinical problem are provided, followed by both common and uncommon case studies that illustrate the role of different imaging modalities, such as ultrasound, radiography, CT, and MRI.